The Effect of Functional Training on Leg Muscle Power for Block Jumps in Volleyball - Muhtar; Komarudin; Bambang Erawan (Universitas Negeri Semarang, 2026)
Improving leg muscle power is essential to support explosive movements in volleyball, particularly for defensive actions such as block jumps. Therefore, a specific and functional training approach is needed to enhance athletes’ lower limb explosive power and optimize blocking performance. This study aims to determine the effect of functional training on leg muscle power for block jumps in volleyball athletes at Tribakti Pangalengan Vocational High School, considering that many adolescent volleyball athletes still experience limitations in vertical jump performance, which affects the effectiveness of blocking techniques during matches. The method used was a pre-experimental One Group Pretest–Posttest with a sample of 15 athletes aged 15–18 years who were selected purposively. The treatment was a functional training program including box jumps, squat jumps, lateral bounds, and Bulgarian split squat jumps carried out for 12 meetings (3 times/week). The instrument for measuring leg muscle power used the Vertical Jump Test with pretest and posttest procedures. The results of the descriptive analysis showed an average increase in vertical jump from 47 cm (pretest) to 53 cm (posttest), with an average difference of 6 cm. The Shapiro–Wilk normality test showed that the data were normally distributed, so the Paired Sample t-Test test was continued which resulted in t = -17.64 and p = 0.000 (p <0.05), which means the increase was statistically significant. These findings are consistent with the literature stating that functional training is effective in increasing explosive strength and movement quality. In conclusion, functional training significantly improves leg muscle power, which supports block jumping ability in volleyball athletes.